Dendrobium derryi (Epidendroideae: Malaxideae): an addition to the flora of India - Gogoi, Khyanjeet (Universidad de Costa Rica, 2024)
Dendrobium derryi has been added to the orchid flora of India from Karbi Anglong district of Assam. This article provides an updated description of the species, accompanied by detailed photos and line drawings based on material collected within the country.